Effect of Planting Distance and Manure Dosage on Growth and Yield of Cayenne Pepper (Capsicum frutescens L.) - Mistaruswan (Contributions of Central Research Institute for Agriculture, 2022)
This study aims to determine the effect of spacing and dose of manure on the growth and yield of cayenne pepper, and whether or not the interaction between the two factors is significant. It was carried out in the experimental garden of the Faculty of Agriculture, Teuku Umar University (UTU) Meulaboh, West Aceh from July to November 2013. The materials used in this study were the Golden phoenix variety, dolomite lime, manure, basic fertilizer Urea, SP-36 and KCl, pesticides Pegasus. The tools used are hoe, machete, elbow, hand spayer, meter, analytical scale, nameplate and other writing instruments. This study used a 3 x 4 factorial randomized block design (RAK) with 3 replications. Factors examined include plant spacing with 3 levels, namely J1 (60 cm x 70 cm), J2 (60 cm x 80 cm) and J3 (60 cm x 90 cm). The manure dose factor is 4 levels, namely P0 (0 tons ha-1) P1 (5 tons ha-1), P2 (10 tons ha-1) and P3 (15 tons ha-1). The variables observed were plant height at 30,45 and 60 DAP, stem diameter at 30, 45 and 60 DAP, number of branches at 30 and 45 DAP, fruit weight and production. The results of the research that have been carried out, that the spacing of plants had a very significant effect on the diameter of the base of the stem at 30 and 45 DAP and the number of branches at 30 DAP, fruit weight and production ha-1. The planting distance had a significant effect on the diameter of the base of the stem at 60 DAP, and had no significant effect on plant height at 30.45 and 60 DAP and the number of branches at 45 DAP. The best cayenne pepper production was found in the treatment (60 cm x 90 cm). The dose treatment of manure had a very significant effect on plant height at 45 and 60 DAP and stem diameter at 45 and 60 DAP, number of branches at 30 and 45 and fruit weight and production of tons ha-1. The dose of manure had a significant effect on plant height at 30 DAP, and no significant effect on stem diameter at 30 DAP. The best cayenne pepper production was found in the treatment (60 cm x 90 cm). There was no interaction between spacing and dose of manure on growth and yield of cayenne pepper.